The Implementation of NHT and GQGA Learning Model to Enhance Student’s Liveliness and Cognitive Learning Outcomes. - Binti Arifah Mardiastuti; Dwi Maryono; Rosihan Ari Yuana (Universitas Sebelas Maret, 2017)
The objectives of the research are: (1) to identify whether the use of Numbered Heads Together (NHT) and Giving Question Getting Answer (GQGA) can improve the students’ activeness in peripheral reparation at X TKJ SMK Muhammadiyah 2 Ngawi in the school year of 2015/2016; (2) to identify whether the use of Numbered Heads Together (NHT) and Giving Question Getting Answer (GQGA) can improve the students’ cognitive learning outcomes at X TKJ SMK Muhammadiyah 2 Ngawi in the school year of 2015/2016. This research was classroom action research which conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection from March until April 2016. The subject of research was the X TKJ grade of SMK Muhammadiyah 2 Ngawi in the school year of 2015/2016. The research data were collected by using techniques of interview, observation, tests (pre-test and post-test), documentation. The qualitative data were validated by using triangulations, and then the quantitative data were validated by using content validity. The qualitative data were analysed by using reduction, presentation, verification, conclusion, and then the quantitative data were analysed by using descriptive statistics. The results showed that the implementation of collaboration NHT and GQGA improved the activeness and cognitive learning outcomes. The percentage of activeness before the implementation of collaboration NHT and GQGA was 19,44%, after that 61,54% in cycle I, and 69,23% in cycle II. The cognitive learning outcomes also increased. The percentage of the qualified students was 38,46%, after that 51,28% in cycle I, and 71,79% in cycle II. From the results above, it can be concluded that the implementation of collaboration NHT and GQGA can improve the activeness and learning outcomes in peripheral reparation at X TKJ students of SMK Muhammadiyah 2 Ngawi in the school year of 2015/2016. This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.